Histological features predictive of liver fibrosis in chronic hepatitis C infection. Issue 12 (December 1996) - Paradis, V; Mathurin, P; Laurent, A; Charlotte, F; Vidaud, M; Poynard, T; Hoang, C; Opolon, P; Bedossa, P
Abstract : AIMS: To assess which pathological features are associated with a sensitive marker of liver fibrogenesis and thus of the potential development of fibrosis in hepatitis C. METHODS: The degree of liver fibrogenesis was evaluated by quantification of type I collagen mRNA and transforming growth factor (TGF) beta 1 mRNA (a major profibrogenic cytokine) in liver biopsy specimens from 28 patients with chronic hepatitis C and five controls, using a quantitative reverse transcription polymerase chain reaction (RT-PCR) assay. Results of mRNA quantification were correlated with histological lesions scored semiquantitatively in the same specimens. RESULTS: Type I collagen mRNA was more strongly expressed in patients than in controls and correlated with the degree of fibrosis, but not with any of the necro-inflammatory lesions (portal inflammation, piecemeal necrosis, and lobular necrosis). TGF beta 1 mRNA concentration was higher in patients than in controls and correlated with histological grade of activity and lobular necrosis. This result was confirmed by in situ hybridisation experiments which showed that TGF beta 1 mRNA was mainly expressed in areas of focal lobular necrosis in chronic hepatitis C. CONCLUSION: This study shows that fibrosis, rather than necro-inflammatory lesions or activity scores, is associated with fibrogenesis and thus with potential aggravation of the fibrous deposit in chronic hepatitis C. Lobular necrosis is an important predictor of prognosis in chronic hepatitis C, as shown by its strong association with TGF beta 1 mRNA expression.